2017
DOI: 10.1002/jat.3505
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of genotoxicity and biodistribution of nano‐ and micron‐sized yttrium oxide in rats after acute oral treatment

Abstract: The increasing use of yttrium oxide (Y O ) nanoparticles (NPs) entails an improved understanding of their potential impact on the environmental and human health. In the present study, the acute oral toxicity of Y O NPs and their microparticles (MPs) was carried out in female albino Wistar rats with 250, 500 and 1000 mg kg body weight doses. Before the genotoxicity evaluation, characterization of the particles by transmission electron microscopy, dynamic light scattering and laser Doppler velocimetry was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 61 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…These studies included a single oral exposure with female Wistar rats, and a 28-day repeated oral exposure study with both male and female Wistar rats. Comet and MN assays for liver and peripheral blood erythrocytes, respectively, were all positive in rats treated with a single dose of Y 2 O 3 , and both single and repeated dose of WO 3 at the highest tested dose (1000 mg/kg body weight) [ 68 70 ]. In rats treated with a repeated dose of Y 2 O 3 , all tests were positive already at 120–480 mg/kg body weight [ 71 ].…”
Section: Literature Quality Evaluation Resultsmentioning
confidence: 99%
“…These studies included a single oral exposure with female Wistar rats, and a 28-day repeated oral exposure study with both male and female Wistar rats. Comet and MN assays for liver and peripheral blood erythrocytes, respectively, were all positive in rats treated with a single dose of Y 2 O 3 , and both single and repeated dose of WO 3 at the highest tested dose (1000 mg/kg body weight) [ 68 70 ]. In rats treated with a repeated dose of Y 2 O 3 , all tests were positive already at 120–480 mg/kg body weight [ 71 ].…”
Section: Literature Quality Evaluation Resultsmentioning
confidence: 99%
“…When this paper (Panyala et al, 2017) was first published, there was a problem with Figure 2. The caption stated that Figure 2G,I showed the normal architecture of the heart and spleen and that Figure 2H,J showed that there was no pathological alterations in the heart and spleen of the Y2 O3 NO‐treated group.…”
Section: Figurementioning
confidence: 99%
“…Following ingestion, translocation of particles into and across the GIT mucosa can occur via four mechanisms: 1) endocytosis, through enterocytes, 2) the M-cell-rich layer of Peyer's patches (small-intestine lymphoid aggregates), 3) persorption, where particles can translocate through a "hole" left in the epithelium when enterocytes shed from the villous tip, and 4) the paracellular route, where NPs pass through weakened tight junctions of the epithelial cell layer. [17][18][19][20] Moreover, NP translocation and interactions with tissues in the GIT can be influenced by size, morphology, hydrophilic-hydrophobic balance, and surface functionalization of the particles in question. For example, it has been suggested that negatively charged materials exhibit poor bioavailability, due to electrostatic repulsion and mucus entrapment.…”
Section: Introductionmentioning
confidence: 99%